Effects of electron beam irradiation on characteristic properties of expanded graphite - Pham Thi, Thu Hong; Nguyen, Thanh Duoc; Nguyen, Thi Ly; Chu, Nhut Khanh; Cao, Van Chung; Doan, Binh; Nguyen, Tuan Kien (Nuclear Science and Technology, 2021)
Vietnamese graphite powder was irradiated by electron beam radiation (EB) at a range of dose from 0 to 120 kGy, then the graphite samples were expanded with a mixture of H2O2:H2SO4 (1,4:20, v/v) incorporating microwave treatment at 700 W for 30 seconds. The characteristic properties of graphite before and after expansion were evaluated by methods of FTIR, Raman, SEM and XRD. Besides the self-assembled of the graphite’s structure after irradiation, the electron beam radiation also facilitated intercalation processing to make expanded graphite, with coefficient of expansion (Kv) 35% higher than that of pristine graphite.